Нестационарное обтекание и аэроупругие колебания рабочих лопаток ступени турбомашины на частичных режимах - Гнесин, Виталий Исаевич; Колодяжная, Любовь Владимировна; Жандковски, Ромуальд; Демченко, Алексей Владимирович (НТУ "ХПИ", 2018)
Предложен численный метод решения связанной задачи нестационарной аэродинамики и упругих колебаний лопаток под действием аэродинамических нагрузок. На основе решения связанной задачи аэроупругости выполнен численный анализ аэроупругого поведения лопаточного венца ротора последней ступени осевой турбины при неравномерном распределении давления за лопаточным венцом. Показано, что колебания рабочих лопаток венца являются устойчивыми с преобладающей частотой близкой к частоте собственной формы колебаний. Предложенный метод решения связанной аэроупругой задачи позволяет прогнозировать амплитудно-частотный спектр колебаний лопаток в потоке газа, включая вынужденные колебания и самовозбуждающиеся (флаттер или автоколебания).

Nonstationary phenomena caused by the blade vibration under the action of disturbing forces that are characterized by the energy exchange between the gas flow and the vibrating blades and make the foundation for a physical mechanism of self-excited oscillations that can either decay (aerodamping) or develop in the stable mode of self-induced vibrations or in the unstable mode of flutter that can result in the construction failure. One of the approaches to an increase in the vibration stability of the blades is the mismatch of eigenmodes and frequencies. Based on the developed mathematical model and the numerical method of aeroelastic behavior of the blade rim in the transonic gas flow (the coupled problem of nonstationary aerodynamics and elastic vibrations of the blades), we gave the numerical analysis of aeroelastic behavior of the turbine blade rim in the three-dimensional flow of ideal gas through the turbine cascade taking into consideration the mismatch of blade eigenmodes and frequencies. To solve the coupled problem we used the partially integral method that includes Euler integral equations and those of the dynamics of vibrating blades (modal approach) at each time step with the information exchange. This method of the solution of coupled aeroelastic problem enables the prediction of the amplitude-frequency spectrum of blade vibrations in the three dimensional flow of ideal gas, including forced vibrations, self-excited vibrations and self-induces vibrations in order to increase the efficiency and reliability of the blade rows of turbine machines. As a result of the investigation we obtained gas dynamic parameters in the form of nonstationary fields, nonstationary loads that have action on the blades and the amplitude and frequency spectra of blade vibrations.
Analysis of nonstationary loadings and vibration amplitudes of the blades of the last turbine cascade taking into consideration the mismatch of eigenmodes
Keywords: метод численный; поток вязкий; автоколебания; задача связанная; нагрузка; флаттер; mathematical model; blade rim; aeroelastic behavior; eigenmode; ideal flow